ANALISA TALI TAMBAT (MOORING) KAPAL PIPE LAY "XXXX" PADA SAAT PEMASANGAN KABEL BAWAH LAUT UNTUK PEMBANGKIT LISTRIK TENAGA ANGIN - Fikri Janitra Adiyatma (2021)
Wind power plants at sea have been widely used in various countries, therefore Indonesia also needs to utilize renewable energy so that it does not cause emissions and is more environmentally friendly. One of them is an offshore wind power plant. PLB ships are used to install the structures and cables needed to distribute electricity ashore. This research is focused on the installation of submarine cables, especially the analysis of moorings for pipe lay barge vessels. The design of the mooring rope configuration must have the ability to hold the underlying structure or submarine cables and pipe lay barge vessels in position. In this analysis using 8 mooring ropes to withstand the effects of extreme wave loads, the analysis is carried out using Orcaflex and Moses software which aims to determine the reaction of moorings during submarine cable installation. Determination of the placement of the mooring point coordinates is very important, so it must pay attention to the distance from the ship to each anchor point by varying the length of the mooring rope and variations in the direction of the waves, besides that in this study an analysis was carried out if the mooring rope broke, the tension on the mooring rope would evaluated according to API RP 2SK and OCIMF. When the mooring rope length is 1000m, the highest tension value is 526.04 kN (53.67 MT) at wave direction 0 mooring rope s3, while when the mooring rope is 600m and the mooring rope tension is 697.31kN (71.15MT), and This value exceeds the standard determined by API RP 2SK which is 55.68 MT or 60% of MBL (minimum breaking load) of 92.8 MT. In the broken mooring rope, the highest tension value in the s3 mooring rope is 870.86 kN (88.86 MT) and this value is not recommended because it exceeds the standard.